Service quality and customer satisfaction in the hotel industry in Serbia - Vujić, Milan; Đorđević, Snežana; Lakićević, Marija (Hotel and Tourism Management, 2019)
The significance of quality measurement and the value of components of a hotel service offer can be observed in the connection with the clients’ satisfaction. The goal of this paper is to measure the level of satisfaction with the quality of hotel service, i.e. to identify the possibilities for establishing and development of long-term relations with the hotel’s clients. Happy guests show a larger degree of satisfaction and loyalty and they visit the hotel again, recommend it to their friends, which affects the hotel’s profits, and the development of tourism as a whole. The research was conducted in eight hotels in Serbia. Primary data were obtained by using survey method and 87 respondents, all of which were the guests of the hotels. The respondents expressed their claims on 7 points of Likert scale. The data analysis was conducted by applying the statistical program IBM SPSS (Statistical Package for the Social Sciences SPSS 20).